Towards an autonomy-supportive model of wellness in Canadian medical education - Neufeld, Adam (Canadian Medical Education Journal, 2022)
Purpose: Learner distress is a huge problem in medicine today, and medical institutions have been called upon to help solve this issue. Unfortunately, the majority have responded not by addressing the system and culture that have long plagued the profession, but by creating individual-focused “wellness” interventions (IFWs). As a result, medical learners are routinely being forced to undergo training on resilience, mindfulness, and burnout. Approach: Grounded in well-supported theory and empirical evidence, my central argument in this commentary is that IFWs are inappropriate, insulting, and psychologically harmful to learners, and that they need to stop. Contribution: Extending prior work in this area, I first present three fundamental problems with IFWs. I then recommend a paradigm shift in how we are approaching “wellness” in medical education. Conclusion: Finally, I provide an evidence-based roadmap, in self-determination theory, for how system-level improvements could be made in a timely, sustainable, and socially responsible way, that would benefit everyone in medicine—from leaders, to educators, to learners, to patients.